2008
DOI: 10.1073/pnas.0712359105
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient and large-scale generation of functional dopamine neurons from human embryonic stem cells

Abstract: We developed a method for the efficient generation of functional dopaminergic (DA) neurons from human embryonic stem cells (hESCs) on a large scale. The most unique feature of this method is the generation of homogeneous spherical neural masses (SNMs) from the hESC-derived neural precursors. These SNMs provide several advantages: (i) they can be passaged for a long time without losing their differentiation capability into DA neurons; (ii) they can be coaxed into DA neurons at much higher efficiency than that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
187
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(200 citation statements)
references
References 32 publications
7
187
0
4
Order By: Relevance
“…Several methods have been reported, with functional improvements in rodent models, but the results have been less successful than had been hoped. [49][50][51][52][53] Several studies 190 REDMOND ET AL.…”
mentioning
confidence: 99%
“…Several methods have been reported, with functional improvements in rodent models, but the results have been less successful than had been hoped. [49][50][51][52][53] Several studies 190 REDMOND ET AL.…”
mentioning
confidence: 99%
“…So far, the most promising results have been obtained using embryonic stem (ES) cells [52][53][54][55][56][57][58][59][60][61][62] or therapeutically cloned ES cells [63]. The examples shown (Fig.…”
Section: Can Stem Cell-derived Neurons Replace Fetal Grafts In Pd Patmentioning
confidence: 99%
“…Other types of stem cells, such as NSCs and progenitors from the embryonic ventral mesencephalon [64][65][66][67], adult NSCs from the subventricular zone [68], bone marrow stromal cells [69], and fibroblast-derived induced pluripotent stem (iPS) cells [61,[70][71][72] have also been used for this purpose. It has also been shown that human stem cell-derived DA neuroblasts, which will be required for patient application, can survive in animal models of PD and after maturation exert functional effects [54,58,66,69,71,72]. However, some properties that will be fundamental for successful clinical translation have not been demonstrated yet for human stem cell-derived DA neurons, including those that they can substantially reinnervate striatum, restore DA release in vivo, and markedly improve deficits resembling the symptoms experienced by patients with PD.…”
Section: Can Stem Cell-derived Neurons Replace Fetal Grafts In Pd Patmentioning
confidence: 99%
“…Such methods established for human ES-derived cells are lineage-specific directed differentiation and selection techniques to generate pure populations of specialised cells. For example, human ES cells have been used to generate functional neurons essential to cure senso-motoric deficits in an animal model of Parkinson's disease (Cho et al, 2008) or to develop insulin-producing cells that reverted glycaemia in diabetic animals (Kroon et al, 2008). At first, these techniques have to be adapted to reprogrammed iPS cells.…”
Section: Requirement ࠻3: Establishment Of Efficient Differentiation Pmentioning
confidence: 99%